Lumbar disc arthroplasty versus anterior lumbar interbody fusion: 5-year outcomes for patients in the Maverick disc investigational device exemption study - Gornet, Matthew F; Burkus, J Kenneth; Dryer, Randall F; Peloza, John H; Schranck, Francine W; Copay, Anne G (Journal of neurosurgery. Spine, 2019)
Despite evidence of its safety and effectiveness, the use of lumbar disc arthroplasty has been slow to expand due in part to concerns about late complications and the risks of revision surgery associated with early devices. More recently, FDA approval of newer devices and improving reimbursements have reversed this trend in the United States. Additional long-term data on lumbar disc arthroplasty are still needed. This study reports the 5-year results of the FDA investigational device exemption clinical trial of the Medtronic Spinal and Biologics' Maverick total disc replacement. Patients with single-level degenerative disc disease from L4 to S1 were randomized 2:1 at 31 investigational sites. In the period from April 2003 to August 2004, 405 patients received the investigational device and 172 patients underwent the control procedure of anterior lumbar interbody fusion. Outcome measures included the Oswestry Disability Index (ODI), numeric rating scales (NRSs) for back and leg pain, the SF-36, disc height, interbody motion, heterotopic ossification (investigational device), adverse events (AEs), additional surgeries, and neurological status. Treatment was considered an overall success when all of the following criteria were met: 1) ODI score improvement ≥ 15 points over the preoperative score; 2) maintenance or improvement in neurological status compared with preoperatively; 3) disc height success, that is, no more than a 2-mm reduction in anterior or posterior height; 4) no serious AEs caused by the implant or by the implant and the surgical procedure; and 5) no additional surgery classified as a failure. Compared to that in the control group, improvement in the investigational group was statistically greater according to the ODI and SF-36 Physical Component Summary (PCS) at 1, 2, and 5 years; the NRS for back pain at 1 and 2 years; and the NRS for leg pain at 1 year. The rates of heterotopic ossification increased over time: 1.0% (4/382) at 1 year, 2.6% (9/345) at 2 years, and 5.9% (11/187) at 5 years. Investigational patients had fewer device-related AEs and serious device-related AEs than the control patients at both 2 and 5 years postoperatively. Noninferiority of the composite measure overall success was demonstrated at all follow-up intervals; superiority was demonstrated at 1 and 2 years. Lumbar disc arthroplasty is a safe and effective treatment for single-level lumbar degenerative disc disease, resulting in improved physical function and reduced pain up to 5 years after surgery.Clinical trial registration no.: NCT00635843 (clinicaltrials.gov).